"I used to be as fit as a linnet" – Beliefs, attitudes, and environmental supportiveness for physical activity in former mining areas in the North-East of England. (February 2015) - Rind, Esther; Jones, Andy
Abstract: Studies of geographical variations in physical activity behaviours have suggested that activity levels are particularly low in areas that have undergone employment loss associated with the decline of industry. This is of concern given that affected populations are already at risk of poor health. Applying focus group methodology amongst 19 participants in four groups, this study aims to unpack how broader societal and environmental changes associated with industrial decline affect beliefs and attitudes towards physical activity in ex-mining communities in the North-East of England. Identified core themes comprise the direct impact of deindustrialisation on social and physical environments. Based on our findings, we provide evidence for mechanisms that operate via loss of occupational physical activity as well as the progressive development of environments that are not fit to support population activity levels. Particularly important was the loss of recreational facilities, public green spaces and sports facilities that were owned and organised by the miners themselves with support from the mining companies. Attitudes and beliefs directly related to the areas' industrial past were also seen to be key. We suggest that the development of interventions considering the socio-cultural history and socio-economic reality of communities could be a promising route to encourage more active lifestyles in deprived areas with particularly low levels of physical activity. Highlights: Reasons for less physical activity previously observed in ex-mining areas unclear. Detailed focus group interviews with community residents to explore influences. Cultures of being physically fit and active present in the past have been lost. Loss of recreational facilities and opportunities associated with colliery closure. Important to consider socio-cultural histories in physical activity interventions.